Perencanaan Strategis Sistem Informasi Manajemen Menggunakan Framework Ward and Peppard Pada Oemah Djari Syariah Hotel and Kitchen - Agustinus Wijaya; Dedrick Kanata Sulistyo (Journal of Information Technology Ampera, 2020)
Oemah Djari is a company engaged in culinary and hospitality. Seeing the increasing population, market demand will certainly increase, in this case the role of Information Systems and Information Technology (IS / IT) is very important to assist in supporting business activities. This study aims to provide a portfolio of information systems at Oemah Djari Syariah Hotel and Kitchen in order to add value effectively and efficiently. In the data collection method, this study uses the interview method with the company's Co Founder. The research method used is Ward and Peppard, using SWOT analysis, Value Chain analysis, Five Force Porter analysis, Critical Success Factor analysis, McFarlan Strategic Grid analysis, and Information Systems Proposal. This research produces recommendations in the form of information system portfolios such as web procurement of Oemah Djari Syariah Hotel and Kitchen, KMS, ERP, SI Marketing, SI Payroll. For further research, it is hoped that discussions will focus more on IT, such as the implementation and development of less than optimal systems.